Extra virgin olive oil inhibits Helicobacter pylori growth in vitro and the development of mice gastric mucosa lesions in vivo - Arismendi Sosa, Andrea Celeste; Mariani, María Laura; Vega, Alba Edith; Penissi, Alicia Beatriz (Frontiers in Microbiology, 2022)
Helicobacter pylori infection is widespread worldwide, with more than a half of the world population infected. H. pylori antibiotic-resistant strains and non-compliance to therapy are the major causes of H. pylori eradication failure. The search for new therapies based on plant extracts is a scientific interest field. The present study was conducted to evaluate the effect in vitro of extra virgin olive oil (EVOO), hydroxytyrosol (HT), and oleuropein (Olp) against two Helicobacter pylori strains and the effect in vivo of the oral administration of EVOO on the gastric mucosa of BALB/c mice infected with this microorganism. The broth microdilution method assayed the antibacterial in vitro activity of EVOO, HT, and Olp against H. pylori strains. For in vivo studies, male BALB/c mice were infected orally with an H. pylori suspension every 72 h. Four groups were used: 1) Control, 2) H. pylori-infected (HP), 3) EVOO, and 4) HP+EVOO. Mice were sacrificed at 7, 15, and 30 days. The stomachs were removed and observed under a microscope. Scoring of the degree of erosion was determined. Samples were processed by histological techniques for light microscopy. Macroscopic analysis showed that the presence of small erosions increased, both in number and size, in the infected group. Animals infected and treated with EVOO exhibited the presence of fewer erosions, which decreased in number as the treatment progressed. The mucosa of the control and EVOO groups showed normal histological characteristics at the three times studied. The mucosa of animals infected with Helicobacter pylori showed disruptions of the lining epithelium, damage to gastric glands, and vasodilation. The mucosa of animals infected with Helicobacter pylori and treated with EVOO showed morphological characteristics similar to those of normal and EVOO mucosa. For the first time, the current study showed the effect in vitro and in vivo of EVOO and combined administration of Ht and Olp against H. pylori using an animal model. Future studies are needed to establish the mechanism of EVOO's action at the gastric mucosa level to propose this product as a natural antimicrobial agent for the treatment of gastric H. pylori infections.